On measuring structural reform - Peter Claeys (Romanian Journal of Fiscal Policy (RJFP), 2015)
Indicators of government activity must be carefully designed to be relevant, credible and accountable. Frustration with reform pressures suggests that measures of policy activity are not providing accurate information. In fact, indicators of product or labour market regulation fail to measure structural reform as they focus on cross-country comparisons rather than on progress with reform over time. I use the novel EU Semester approach recommending EU Member States to implement reforms and their annual follow-up in the National Reform Programme to develop some indicators of how reform plans are actually implemented. This indicator might be useful for checking progress with policy, but also for empirical studies testing what drives or blocks reform in different policy domains.
Keywords: C89; E69; H00; H89; 330; structural reform; regulation; indicator; fiscal policy; EU